The Relationship between Pregnant Mothers' Behavior and Adherence to Folic Acid Consumption - Ahmar, Hamdiah; Mulalinda, Andhika Muhammad Fadhly; Jabiy, Filvanus; Ernawati, Ernawati; Suryani, Naning (Babali Nursing Research, 2024)
Introduction: Pregnancy, defined as the state in which a woman carries an embryo in her uterus for approximately 38 to 40 weeks from the first day of menstruation. According to WHO standards, the normal pregnancy period ranges from 37 to 42 weeks. Prenatal care is highly recommended to reduce the risk of fetal death and complications. Folic acid supplementation during pregnancy is considered crucial in preventing neural tube defects and congenital abnormalities, with WHO recommending supplementation as a preventive measure. Despite evolving information on the benefits of folic acid, the compliance level of pregnant women remains low. Therefore, this research becomes an interesting exploration. The research aims to explore the behavior of pregnant women regarding compliance with folic acid consumption in the working area of Malawei Public Health Center, Manoi District, Sorong City. Methods: The applied method is an analytical design with a Cross-Sectional approach, conducted from May to July 2023. The study population involved 197 first-trimester pregnant women, with a sample size of 70 respondents selected using accidental sampling. Data were analyzed using the chi-square test. Results: Findings indicate that the majority of respondents are aged 20-35 years, unemployed, have a high school education, and income ranging from Rp1,000,000 to Rp5,000,000. 58.6% of pregnant women exhibited sufficient behavior, and 85.7% of them were classified as compliant in consuming folic acid. The chi-square test analysis shows a significant relationship between the behavior of first-trimester pregnant women and compliance with folic acid consumption, with a p-value of 0.004, indicating that the p-value is < 0.05. Conclusion: There is a correlation between the behavior of pregnant women and the extent to which they comply with folic acid consumption. The implication of this research is the need for the development of interventions or health education programs focused on improving the behavior of pregnant women to enhance compliance with folic acid consumption during pregnancy.